2011
DOI: 10.3109/00048674.2010.543653
|View full text |Cite
|
Sign up to set email alerts
|

Kessler Psychological Distress Scale: Normative Data from the 2007 Australian National Survey of Mental Health and Wellbeing

Abstract: These data may be helpful for clinicians and researchers alike in understanding the likelihood of mental disorder in a given individual or sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
287
10
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 307 publications
(320 citation statements)
references
References 39 publications
18
287
10
5
Order By: Relevance
“…For example, it has been found that gender is associated with psychological distress (Slade, et al, 2011) and that gender has an effect on gambling treatment outcomes (Crisp et al, 2000;Petry et al, 2006). By accounting for these effects, more consistent estimates may be obtained across future studies involving gambling disorders.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…For example, it has been found that gender is associated with psychological distress (Slade, et al, 2011) and that gender has an effect on gambling treatment outcomes (Crisp et al, 2000;Petry et al, 2006). By accounting for these effects, more consistent estimates may be obtained across future studies involving gambling disorders.…”
Section: Discussionmentioning
confidence: 98%
“…For each K10 stratum, the likelihood of Composite International Diagnostic Interview-defined ICD-10 diagnosis of an affective disorder or anxiety disorder in the previous 12 months was calculated for the study sample. A Bayesian approach was used as recommended by Slade et al (Slade, et al, 2011) where prior probabilities for comorbid anxiety and affective disorders were 37.4% and 37.9% respectively (Lorains, et al, 2011). Post-test odds for each condition were then calculated from the product of pre-test odds (prior probability of condition / (1 -prior probability of condition)) and stratum specific likelihood ratios based on Australian normative data (Slade, et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Este envolve sintomas do foro depressivo e ansioso, tais como baixa autoestima, sentimentos de desesperança, ansiedade, agitação e tristeza, experienciados pelo individuo física e psicologicamente. Entre outros, o DP tem sido sugerido como um relevante indicador de fatores como a presença e/ou desenvolvimento futuro de psicopatologia, da qualidade de vida, do planeamento apropriado do tipo e forma de tratamento e, até, da evolução associada ao mesmo (Pai, Drotar, Zebracki, Moore, & Youngstrom, 2006;Ritsner, Modai, & Ponizovsky, 2002;Simard, Hudon, & Reekum, 2009;Slade, Grove, & Burgess, 2011;Van den Broeck, D'Hooghe, Enzlin, & Demyttenaere, 2010).…”
unclassified